GIG WORKERS: Assessing the impact on local government. - Franzel, Joshua; Young, Gerald; Liss-Levinson, Rivka (Public Management (00333611), 2018)
The article focuses on capability of information and communication technology which have become more advance sector of economy in the wake of the Great Recession. Topics discussed include increment of long term legacy benefit costs for gig or contingent worker; the U.S. Bureau of Labor Statistics (BLS); and proposal of contingent work by labor economist Audrey Freedman in 1985 related to conditional and transitory employment arrangements.